ANTIBODIES TO BENZO(A)PYRENE AND STEROID HORMONES IN WOMEN WITH NON-DEVELOPING PREGNANCY - Гюлай Агамуса кызы Сафарова; Марина Борисовна Игитова; Юрий Владимирович Кореновский; Елена Геннадьевна Поленок (The Publishing House Medicine and Enlightenment, 2020)
The levels of immunoglobulins of class A (IgA) and G (IgG) to estradiol (Es), progesterone (P) and benzo[a]pyrene (Bp) were determined in women who had undergone one or more episodes of non-developed pregnancy, including 50 patients with sporadic cases and 20 patients with normal reproductive losses compared to 30 patients in the control group. Significant differences were found in the level of antibodies to estradiol (IgA 5.27 ± 2.87 vs. 3.26 ± 1.69, p = 0.001; IgG 10.52 ± 6.97 vs. 7.08 ± 4.06, p = 0.019), progesterone (IgA 3.13 ± 1.49 vs. 2.29 ± 1.17, p = 0.012; IgG 8.05 ± 5.61 vs. 5.48 ± 3.65, p = 0.033) and benzo[s]pyrene (IgA 4.55 ± 2.12 vs. 4.44 ± 2.06, p = 0.818; IgG 11.76 ± 6.09 vs. 8.77 ± 4.65, p = 0.047) in patients with sporadic non-developed pregnancy compared to women without reproductive loss, while in patients with habitual unbearable pregnancy the values were comparable for antibodies to estradiol (IgA 11.76 ± 6.09 vs. 3.26 ± 1.69, p = 0.749; IgG 8.12 ± 6.28 vs 7.08 ± 4.06, p = 0.749), progesterone (IgA 2.79 ± 1.163 vs 2.29 ± 1.17, p = 0.229; IgG 2.79 ± 1.163 vs. 5.48 ± 3.65, p = 0.573) and pyrene-free (IgA 4.65 ± 2.57 vs. 4.44 ± 2.06, p = 0.749; IgG 8.76 ± 6.19 vs. 8,77 ± 4,65, p = 0.994).